2021
DOI: 10.33141/po.2021.07.01
|View full text |Cite
|
Sign up to set email alerts
|

Zachowania konsumentów w czasie pandemii COVID-19

Abstract: Artykuł ma charakter empiryczny i zawiera przegląd literatury oraz wyniki badań własnych na temat zachowań konsumentów w czasie pandemii COVID-19. Celem artykułu jest diagnoza skali i kierunków zmian polskich konsumentów w zakresie nabywania, użytkowania i pozbywania się produktów. Badania przeprowadzono na kwotowo wybranej próbie 750 respondentów dobranych ze względu na wiek, płeć i wykształcenie. Badania potwierdzają światowe trendy zachowań konsumenckich w zakresie paniki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
3
5
0
Order By: Relevance
“…No statistically significant differences were observed across age groups ( p > 0.05). Similar results were obtained by Chlipala and Żbikowska [ 129 ] in a survey of 750 respondents in Poland, where 59.7% of participants indicated that they purchased as much meat and cold cuts as before the pandemic. Only 23.3% reported buying less of these products, while 10.3% increased their purchases of meat and cold cuts [ 129 ].…”
Section: Meat and Meat Products Market In The Covid-19 Periodsupporting
confidence: 86%
See 1 more Smart Citation
“…No statistically significant differences were observed across age groups ( p > 0.05). Similar results were obtained by Chlipala and Żbikowska [ 129 ] in a survey of 750 respondents in Poland, where 59.7% of participants indicated that they purchased as much meat and cold cuts as before the pandemic. Only 23.3% reported buying less of these products, while 10.3% increased their purchases of meat and cold cuts [ 129 ].…”
Section: Meat and Meat Products Market In The Covid-19 Periodsupporting
confidence: 86%
“…Similar results were obtained by Chlipala and Żbikowska [ 129 ] in a survey of 750 respondents in Poland, where 59.7% of participants indicated that they purchased as much meat and cold cuts as before the pandemic. Only 23.3% reported buying less of these products, while 10.3% increased their purchases of meat and cold cuts [ 129 ]. In a survey of 1048 South Carolina consumers conducted in November 2020, Richards and Vassalos [ 46 ] found that the majority (58%) did not alter their local meat (products that are farm-raised in South Carolina within 200 miles of the customer’s home or produced in North Carolina and Georgia within a short distance from the South Carolina border) consumption habits.…”
Section: Meat and Meat Products Market In The Covid-19 Periodsupporting
confidence: 86%
“…The largest group of people (43%) who reduced their visits to stationary shops for grocery shopping as a result of the pandemic were customers aged 25-39. In contrast, research by P. Chlipała and A. Żbikowska [87] shows that in Poland, a small proportion of consumers, during the COVID-19 pandemic, bought food online, while a significant group of consumers (over 40%) sourced their groceries from shops near their place of residence. In addition, the frequency of grocery shopping increased during this period.…”
Section: Food Purchase and Food Wastagementioning
confidence: 93%
“…Changes in food consumption in Poland do not fully coincide with changes observed in other countries. Research conducted in Poland shows that, during the COVID-19 pandemic, changes in purchase volumes can be considered insignificant [87]. However, it is worth noting that about one-fourth of Polish consumers declared that more fruit and vegetables were purchased in their households.…”
Section: Food Purchase and Food Wastagementioning
confidence: 99%
See 1 more Smart Citation